Rho-Kinase Accelerates Synaptic Vesicle Endocytosis by Linking Cyclic GMP-Dependent Protein Kinase Activity to Phosphatidylinositol-4,5-Bisphosphate Synthesis - Taoufiq, Zacharie (J Neurosci, 2013)
Rho-kinase plays diverse roles in cell motility. During neuronal development, Rho-kinase is involved in neuronal migration, and in neurite outgrowth and retraction. Rho-kinase remains highly expressed in mature neurons, but its physiological roles are poorly understood. Here we report that Rho-kinase plays a key role in the synaptic vesicle recycling system in presynaptic terminals. Vesicles consumed by excessive exocytosis are replenished by accelerating vesicle endocytosis via a retrograde feedback mechanism involving nitric oxide released from postsynaptic cells. This homeostatic control system involves presynaptic cyclic GMP-dependent protein kinase (PKG) and a plasma membrane phospholipid, phosphatidylinositol-4,5-bisphophate (PIP(2)). We found that application of a Rho-kinase inhibitor, a PKG inhibitor or both, reduced the PIP(2) content in Wistar rat brainstem synaptosomes to a similar extent. Likewise, application of the Rho-kinase inhibitor into the calyx of Held presynaptic terminal slowed vesicle endocytosis to the same degree as did application of the PKG inhibitor. This endocytic slowing effect of the Rho-kinase inhibitor was canceled by coapplication of PIP(2) into the terminal. By contrast, a RhoA activator increased the PIP(2) content and reversed the effect of the PKG inhibitor in brainstem synaptosomes. The RhoA activator, when loaded into calyceal terminals, also rescued the endocytic slowing effect of the PKG inhibitor. Furthermore, intraterminal loading of anti-PIP(2) antibody slowed vesicle endocytosis and blocked the rescuing effect of the RhoA activator. We conclude that Rho-kinase links presynaptic PKG activity to PIP(2) synthesis, thereby controlling the homeostatic balance of vesicle exocytosis and endocytosis in nerve terminals.